Instant penetration testing : setting up a test lab how-to : set up your own penetration testing lab using practical and precise recipes - Fadyushin, Vyacheslav (Instant : short, fast, focused, 2013)
Filled with practical, step-by-step instructions and clear explanations for the most important and useful tasks. Get the job done and learn as you go. A how-To book with practical recipes accompanied with rich screenshots for easy comprehension. This is a How-to guide, written with practicality in mind. Theory is downplayed, and we get you started doing the things you need to do, right away. ""Instant Penetration Testing: Setting Up a Test Lab How-to"" is written for beginners to penetration testing, and will guide you in avoiding the common mistakes that people new to penetration testing make.